The effect of social media marketing, electronic word-of-mouth, brand image on purchase intention - Ramadhan, Aldan Mutia; Millanyani, Heppy (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Social media has the huge impact nowadays era. Every sector uses social media as one tool to engaged with to viewer instead of marketing.  This research focuses on the process of selecting a coffee shop, exploring the influence of factors such as social media marketing, brand image, and eWOM on consumer purchase intention. The study employs the SEMPLS method to investigate the relationships between Social Media Marketing, eWOM, Brand Image, and Purchase Intention among consumers in Kuningan. Data were collected from consumer responses in Kuningan. This research is using quantitative approach, data collected using a questionnaire with the sample size comprises 150 consumers in Kuningan. Whereas it. Findings indicate that social media marketing significantly influences purchase intention, brand image, and electronic word-of-mouth (eWOM) within the coffee industry of Kuningan. Positive eWOM correlates with higher purchase intentions. However, contrary to expectations, brand image did not demonstrate a significant impact on purchase intention. For coffee shop owner, these findings offer actionable insights into crafting effective marketing strategies tailored to the unique dynamics of smaller town contexts. By understanding and leveraging these nuances, businesses can better position themselves amidst fierce socicompetition, ultimately enhancing their market presence and consumer appeal.